Elements of Complexity Science in the Computer-Based Assessment of Athletes’ Performances - Raţă, G.; Raţă, E.; Milici, M. R. (Elektronika ir Elektrotechnika, 2010)
In this article, on the basis of analysis of extensive scientific and factual materials, a hypothesis will be formulated providing answers to the noted questions and allowing predictions to be made for both the immediate future of the evolution of the sports records as well as the general direction of evolution in the far distant future. Knowing that the evolution of the human performances is made through leaps, the time periods for which it is made the approximation must be longer than the time between two performance leaps of the tested sportsman, but at the same time must not include more than three evolutions bearing because the prediction for a too longer time can’t be made. Ill. 5, bibl. 9 (in English; abstracts in English, Russian and Lithuanian).